PG123 Insitu simulation: changes to resuscitation practice – living in a covid-19 world. (10th November 2020) - Harrison, Tracey; Flockton, Eve
Abstract : Background: The outbreak of COVID -19 has had catastrophic impact on healthcare throughout the world and as a result has altered the delivery of many clinical procedures. Covid -19 is thought to spread from person to person through close contact and droplets, aerosol transmission can also occur. During CPR there is the risk of exposure to bodily fluids and for procedures including chest compressions, intubation or ventilation to generate infectious aerosol. As a result, the Resuscitation Council UK recommends that for all aerosol generating procedures, personal protective equipment must be worn by all members of the resuscitation team before entering the area and CPR commencing. Summary of Work: As a result of this considerable change to practice it was acknowledged there was a need for staff to have the opportunity to practice these changes. We offered an insitu simulation programme to all the wards and departments throughout BTHFT focussing on ED, Renal, AMU and Care of the Elderly wards and departments. We ran a simple deteriorating patient scenario leading to a shockable cardiac arrest. Summary of Results: Despite numerous communications issued relating to the changes to practice staff appeared unfamiliar with the new procedure. Many were uncomfortable with the new practice but all involved expressed their appreciation for the opportunity to take part in a session and improve their knowledge. The sessions allowed staff to ask questions about the new procedure and ensured that they were familiar with the updates. To date we have run a total 19 sessions, with further planned. Approximately 100 staff members from the multi-disciplinary team accessed the sessions with 4–5 staff attending each session. Qualitative feedback from staff included comments such as 'time taken to don PPE', 'reminders on the use of the defib' and 'excellent to be able to practice this in the clinical area'. Feedback was collated via feedback forms following the individual sessions. Conclusions and Recommendations: Despite written communications being sent to all staff within the organisation it became obvious that many staff did not access these or were aware of the changes to the resuscitation procedure. By delivering a training session in the clinical area allowed staff the opportunity to take part in a 'hands on' simulated safe learning environment. It is our recommendation that when a significant change to clinical practice is made this is reinforced with an insitu simulation programme.